Ethics of Artificial Intelligence in Education - Gartner, Smiljana; Krašna, Marjan (Revija za elementarno izobraževanje, 2023)
The post-COVID period drastically accelerated the development and increased use of artificial intelligence. These changes have not been limited to industry but have begun to be introduced into education. The digital literacy of all involved in education must also incorporate ethical considerations related to the application of AI in education. The article presents the ethical codes of AI and analyse the four basic building blocks of an ethical attitude towards AI in education (autonomy, privacy, trust and responsibility). Understanding the concepts of AI and their ethical implications is a condition for acting in accordance with them and for their introduction in education.